Profit-led and export-led accumulation regimes in Chinese manufacturing firms - Xiaodan Yu; Giovanni Dosi; Maria Enrica Virgillito; Can Huang; Lanhua Li (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
By means of a fine-grained dataset linking exported product-level and firm-level data, this pa- per reconstructs the Chinese accumulation regimes at the microlevel in the period 2000-2013. After documenting a few macro stylized facts on the Chinese export-led accumulation regime in terms of the trend of Chinese exports in international markets, and the appreciation in the terms of trade in manufacturing products, the paper gives evidence of a process of restructuring of exporting firms towards more complex products and sectors, against any hypothesis of a purported price dumping in international markets. The positive relationship between technological content of the exported product and pricing markup strategies confirms the Sylos-Labini hypothesis linking prices and technological advantage, yielding the formation of international oligopolies able to exercise forms of market power and setting prices well-above any competitive level. As such, the trend in export prices has signalled the progressive capacity of the Chinese firms to orient the patterns of international market penetration, particularly in most complex productions
Keywords: P00; E24; F14; 330; Chinese exports; product/firm level export prices; pass-through; international oligopolies; profitabilities